Reversibility of artifacts of fluid volume measurements by bioimpedance caused by position changes during dialysis - Fenech, M; Jaffrin, M Y; Malmen, U (Université d'Ottawa | University of Ottawa, 2002)
The effect of temporary position changes, sitting up from supine, on extracellular (ECW) and intracellular (ICW) resistances and fluid volumes calculated from whole body bioimpedance using a Xitron 4200 impedancemeter was investigated on 8 patients during dialysis for a total of 11 tests. It was found that ECW resistance decreased instantaneously by an average of 2.3% when the patient sits up, due to plasma and interstitial fluid shift into the legs which decreases leg resistance, the major contributor to total resistance. This drop in resistance is incorrectly interpreted by the device as an increase in ECW volume which averages 235 ml. But this effect is completely reversible and both ECW resistance and fluid volume rapidly resume their normal course when the patient returns to his initial position. No significant variation in ICW resistance was observed in any of the patients at the position change. We conclude that segmental impedance, which has been proposed to minimize this artifact, is not advisable in dialysis monitoring and that it is simpler to ignore or switch off measurements during the position change so that later data are not affected by it.
Keywords: Aged; Artifacts; Extracellular Space; Female; Fluid Shifts; Humans; Male; Middle Aged; Posture; Electric Impedance; Renal Dialysis